Signal and Information Processing, Networking and Computers Proceedings of the 5th International Conference on Signal and Information Processing, Networking and Computers (ICSINC) - Sun, Songlin; Fu, Meixia; Xu, Lexi (Lecture Notes in Electrical Engineering, 2019)
This proceedings book presents selected papers from the 5th Conference on Signal and Information Processing, Networking and Computers (ICSINC), held in Yuzhou, China, from November 29 to December 1, 2018. It focuses on the current research in a wide range of areas in the fields of information theory, communication systems, computer science, signal processing, aerospace technologies, and other related technologies. With contributions from experts from both academia and industry, it is a valuable resource for anyone who is interested in this field.